2019
DOI: 10.1038/s41598-019-46085-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical shear controls bacterial penetration in mucus

Abstract: Mucus plays crucial roles in higher organisms, from aiding fertilization to protecting the female reproductive tract. Here, we investigate how anisotropic organization of mucus affects bacterial motility. We demonstrate by cryo electron micrographs and elongated tracer particles imaging, that mucus anisotropy and heterogeneity depend on how mechanical stress is applied. In shallow mucus films, we observe bacteria reversing their swimming direction without U-turns. During the forward motion, bacteria burrowed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 58 publications
5
42
0
Order By: Relevance
“…It is also believed that the helical cell shape of both H. pylori and Campylobacter jejuni , which colonizes the thick mucus layer of the cecum, facilitates mucus penetration by allowing the body to push against the mucin matrix like a corkscrew ( 34 , 35 ). Recent work demonstrated that the peritrichous rod-shaped bacteria Escherichia coli and Bacillus subtilis can penetrate cervical mucus by taking advantage of water channels created by shear forces during secretion ( 36 ). The behavior of V. cholerae in mucus has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…It is also believed that the helical cell shape of both H. pylori and Campylobacter jejuni , which colonizes the thick mucus layer of the cecum, facilitates mucus penetration by allowing the body to push against the mucin matrix like a corkscrew ( 34 , 35 ). Recent work demonstrated that the peritrichous rod-shaped bacteria Escherichia coli and Bacillus subtilis can penetrate cervical mucus by taking advantage of water channels created by shear forces during secretion ( 36 ). The behavior of V. cholerae in mucus has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many biological fluids, such as mucus, DNA solutions, or suspensions of long viruses exhibit a certain degree of liquid crystallinity [12][13][14][15][16] . Liquid crystallinity and mechanical shear also can control bacteria penetration in mucus 17 . Besides the theoretical importance, studies of bacteria motility in complex fluids provide clues in the propagation of bacteria-born diseases and colonization of tissues by pathogens.…”
mentioning
confidence: 99%
“…Bacterial penetration into meat and leafy vegetables with sessile drops were mathematically modeled previously (22)(23)(24). Bacterial migration in colon mucus and to the epithelial layer was investigated (25). The effect of chemotaxis on host infection and pathogenicity was also reviewed (26).…”
Section: Literature About Mathematical Modeling and Experimental Studies Of Bacterial Penetration In The Gastrointestinal Tractmentioning
confidence: 99%